Preliminary assessment of some annual Ethiopian Trifolium species for hay production - Kahurananga, J.; Tsehay, A. (1984)
The dry matter yields of 22 accessions of 7 native annual Trifolium species from the Ethiopian highlands were evaluated for hay production at Shola near Addis Ababa, Ethiopia (altitude 2380 m and latitude 9°02' N). DM yields obtained at a fertiliser rate of 40 kg ha-1 ranged from 1473 kg ha-1 for an unidentified species to 6820 kg ha-1 for T. tembense while, unfertilised yields were between 436 kg ha-1 and 1330 kg ha-1